Pemahaman Investasi Bodong bagi Pelaku Usaha Mikro di Indonesia - Ascaryan Rafinda; Agus Suroso; Sausan Nuhaa Maisarah; Sugiarto Sugiarto; Ascariena Rafinda (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This community engagement initiative aims to enhance the understanding of micro-enterprises in Indonesia regarding the dangers of fraudulent investments, which are increasingly prevalent and often target small business groups with promises of high returns. The target audience includes micro-entrepreneurs in the [insert location], who typically have limited access to financial literacy and reliable investment information. The implementation methods involved face-to-face and online sessions, including awareness campaigns, interactive discussions, and simulations to identify characteristics of illegal investments. The results indicate a significant improvement in participants’ understanding of fraudulent investment schemes, the importance of investment institution legality, and preventive steps to avoid financial scams. This program also produced a simple educational module that can be independently used by micro-entrepreneurs. The activity underscores the importance of collaboration between academics, local governments, and financial institutions in strengthening the financial literacy resilience of the public, particularly within the vulnerable micro-enterprise sector.